2018
DOI: 10.3390/jcm7100338
|View full text |Cite
|
Sign up to set email alerts
|

The CHA2DS2-VASc Score Predicts Major Bleeding in Non-Valvular Atrial Fibrillation Patients Who Take Oral Anticoagulants

Abstract: Background: Patients with atrial fibrillation (AF) are at a substantial risk of ischemic stroke. The CHA2DS2-VASc score predicts the risk of thromboembolism, but its role in predicting major bleeding in patients taking oral anticoagulants is unclear. Methods: We used the National Health Insurance Research Database (NHIRD) of Taiwan to identify patients with AF from 2010 to 2016. They were divided into four groups according to the oral anticoagulants. The outcomes were ischemic stroke/systemic thromboembolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
8
2
Order By: Relevance
“…These result indicated that AF patients with score 0-1 might be induced bleeding by warfarin. The result was not consistent with previous ndings [19]. They found that the high rates for bleeding events happened in the patients at score ≥ 5.…”
Section: Discussioncontrasting
confidence: 89%
“…These result indicated that AF patients with score 0-1 might be induced bleeding by warfarin. The result was not consistent with previous ndings [19]. They found that the high rates for bleeding events happened in the patients at score ≥ 5.…”
Section: Discussioncontrasting
confidence: 89%
“…The CHA 2 DS 2 -VASc score was introduced for risk stratification of systemic and cerebral ischaemic events in AF patients. Furthermore, it was shown that this score is useful to predict the overall bleeding risk in AF cohorts [14]. A retrospective study conducted comparative validation of the 6-month GRACE (Global Registry of Acute Coronary Events) risk score and CHA 2 DS 2 -VASc risk score to predict the risk of post-ACS ischaemic stroke [15].…”
Section: Discussionmentioning
confidence: 99%
“…CHA 2 DS 2 ‐VASc Score has also been shown to predict major bleeding events in non‐valvular AF patients 30 . In our elderly NSTEACS cohort, patients with score > 4 on admission showed a trend toward higher major bleeding and need for transfusion, though they received less antithrombotic treatments and there were no differences about previous bleeding.…”
Section: Discussionmentioning
confidence: 73%